Meningkatkan Kemampuan Motorik Halus Anak Usia 5-6 Tahun Melalui Penerapan Metode Drill Kegiatan Menggambar - Sriyani Sulistiyowati; Joni Joni; Rizki Amalia (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the low fine motor skills of children aged 5-6 years at Bhakti Pertiwi Kindergarten, Kampar Regency. For this reason, a concrete application is needed to be able to find the right way regarding children's fine motor skills, namely the application of the drawing Drill method. This type of research is classroom action research which is an examination of learning activities in the form of actions, which are deliberately created and occur in a class together with a total of 15 children consisting of 7 boys and 8 girls. . Data collection techniques for data collection in this research are observation and documentation. The data analysis technique used in this research is the percentage technique. From the results of classroom action research and discussions as described, the conclusion regarding the results of this research is that the application of the drawing Drill method can improve the fine motor skills of children aged 5-6 years at Bhakti Pertiwi Kindergarten, Kampar Regency. Children's fine motor skills can be seen from the Precycle, which is in the "Not Developed" criteria, namely 9 children or 75%. After the action in cycle I, namely through the drawing Drill method, there was an increase, namely reducing to 1 child or 8.33%. The "Starting to Develop" criteria increased from Precycle 3 children or 25% to 3 children or 25% and increased again in cycle II to 1 child or 8.33%. In the "Developing According to Expectations" criterion, there was not a single child in this criterion, increasing to 8 children or 66.67% and increasing again in cycle II to 1 child or 8.33%. The "Very Well Developing" criteria increased from none in the first cycle, none in the first cycle and increased again in the second cycle to 10 children or 83.33% Keywords: Drill Method, Drawing Activities, Fine Motor Skills of Children 5-6 Years of Age